Perlindungan Hukum bagi Wajib Pajak dalam Sengketa Pajak Daerah di Kabupaten Badung - A.A Gede Diotama; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2022)
During the search for justice in the field of taxation, the legislation has facilitated a special route. The emergence of tax disputes is the result of decisions that do not give satisfaction to taxpayers, so efforts need to be made to resolve them properly, effectively, and efficiently. The purposes of this study are to reveal the efforts of taxpayers' objections and appeals in resolving local tax disputes in Badung Regency, taxpayers' lawsuits in resolving regional tax disputes and the chronology and analysis of tax dispute resolution in Badung Regency. This research is a type of normative research with a statutory approach. Sources of data used in the form of primary and secondary legal sources. The data collection technique used in this research is the technique of studying legal documents and the data that has been collected is then used qualitative analysis techniques. The results of the study reveal that the settlement of local tax disputes between taxpayers and the Badung Regency Government through preventive and repressive efforts, forms of legal protection in resolving local tax disputes can be in the form of preventive and repressive legal protection, as well as legal efforts carried out by taxpayers to decide cases of local tax disputes in Indonesia. Badung Regency through preventive efforts by submitting an objection to the Head of the Badung Regent against the tax underpayment assessment letter.